1993
DOI: 10.1021/ac00052a012
|View full text |Cite
|
Sign up to set email alerts
|

Toxin detection using a tyrosinase-coupled oxygen electrode

Abstract: An enzyme-based "electrochemical canary" is described for the detection of cyanide. The sensing system imitates cyanide's site of toxicity in the mitochondria. The terminal sequence of electron transfer in aerobic respiration is mimicked by mediator coupling of tyrosinase catalysis to an electro-chemical system. An enzyme-coupled oxygen electrode is created which is sensitive to selective poisoning. Biocatalytic reduction of oxygen is promoted by electrochemically supplying tyrosinase with electrons. Thus, fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…Thus, OPH could be combined with an optical transducer to measure the absorbance of p-nitrophenol or with an amperometric transducer to monitor the oxidation or reduction current of this product [26]. With a different approach, the capability of various pesticides such as cyanide [27], diethyldithiocarbamates [28], and hydrazines [29] to inhibit the enzyme tyrosinase was also reported. Similarly, diazinon and dichlorvos were detected at limits around 5 µM and 75 µM, respectively, using a tyrosinase-based oxygen sensor [30].…”
Section: Biocidesmentioning
confidence: 99%
“…Thus, OPH could be combined with an optical transducer to measure the absorbance of p-nitrophenol or with an amperometric transducer to monitor the oxidation or reduction current of this product [26]. With a different approach, the capability of various pesticides such as cyanide [27], diethyldithiocarbamates [28], and hydrazines [29] to inhibit the enzyme tyrosinase was also reported. Similarly, diazinon and dichlorvos were detected at limits around 5 µM and 75 µM, respectively, using a tyrosinase-based oxygen sensor [30].…”
Section: Biocidesmentioning
confidence: 99%
“…It is used for estimation of pollution in the course of wineproduction but in the same way can be discovered traces from sulfide ions in the food (93). For the determination of level of toxivity of the biological liquids water and industrial waste water are developed different variants of biosensors. One of them is with the Clark electrode and tirozine (94), which allowed to discover some traces of cyanide by the impulse inhibitor method. The other kind is a miniature ISFET -biosensor with peroxidase (95).…”
Section: Biosensors For Ecologymentioning
confidence: 99%
“…Amelioration of this deterioration in signal is under investigation by addressing the enzyme activity using a potential pulsing strategy [3] thus minimizing oxygen depletion.…”
Section: Immobilized Enzyme Inhibition Electrodementioning
confidence: 99%
“…This study utilized a dual electrode strategy for the electrochemical generation of substrate (H202) at one electrode and detection of the solution mediator, ferrocene, at the second electrode. In an innovative approach Smit and Rechnitz [3] have replaced the respiratory enzyme CCO with tyrosinase, which is also inhibited by the respiratory poisons. They reported that the natural substrate for the tyrosinase enzyme could be replaced with an electrochemically regenerable solution redox species, ferrocyanide, that can act as an electron donor in the enzymatic reduction of oxygen, for the development of a 'reagentless' enzyme electrode for respiratory poisons which consumes only oxygen.…”
Section: Introductionmentioning
confidence: 99%